15 The effect of different communication strategies about stopping cancer screening on inyention to screen and cancer anxiety: a randomised online study in older adults. (4th December 2019) - Smith, Jenna; Dodd, Rachael; Hersch, Jolyn; Cvejic, Erin; McCaffery, Kirsten; Jansen, Jesse
Abstract : Background and aims: Older adults (≥65 years) who routinely screen for cancer are less likely to benefit and more likely to be harmed by overdiagnosis than those who are younger. Therefore, general practitioners (GPs) may recommend that older adults stop cancer screening. Recent qualitative work has identified older adults' preferences for different communication strategies about stopping screening. This study experimentally tested the effect of communication strategies on screening intention and cancer anxiety. Methods: 271 participants (135 male and 136 female) aged 65 to 90 years were recruited from an online panel. They were asked to imagine a conversation with their GP about stopping cancer screening (breast for women, prostate for men). Participants were randomised to receive one of four statements about stopping screening at Time 1: (1) control (' this screening test would harm you more than benefit you '); (2) health status (' your other health issues should take priority' + control statement); (3) negatively framed life expectancy (' you may not live long enough to benefit from this test ' + control statement) or (4) positively framed life expectancy (' this test would not help you live longer ' + control statement). At Time 2 participants received a second scenario where the GP further explained the recommendation to stop screening by addressing how this contradicts previous positive screening messages and why recommendations have changed (addressing anchoring frame bias). Primary outcomes (screening intention and cancer anxiety; scale of 1 to 10) and secondary outcomes (trust in GP, trust in information provided by GP, trust in the healthcare system, decisional conflict and knowledge) were measured at Time 1. Primary outcomes and knowledge were measured again at Time 2. Results: No overall main effects were significant for screening intention or cancer anxiety. However, post-hoc contrasts of the greatest differences between conditions revealed screening intention was significantly lower in the negatively framed life expectancy condition compared to health status condition (5.98 vs. 7.05, p =.049) and cancer anxiety was significantly lower in the negatively framed life expectancy compared to positively framed life expectancy condition (4.83 vs. 5.82, p =.025). Trust in GP was significantly higher in the negatively framed life expectancy condition compared to the positively framed life expectancy condition (4.62 vs. 4.38, p =.037) and control (4.64, p =.022), and those in the negatively framed life expectancy condition felt significantly clearer about their values than those in the control (7.58 vs 14.79, p =.049) or positively framed life expectancy condition (15.81, p =0.27). Explaining the changed recommendation significantly reduced both screening intention (mean difference=0.80, p =.044) and cancer anxiety (mean difference=0.26, p =.034) between Time 1 and Time 2. Conclusion: Older adults may be more willing to reduce their screening without experiencing more cancer anxiety when GPs communicate that they may not live long enough to benefit from screening and explicitly explain why this information contradicts previous positive messages about cancer screening. Further research on communication strategies in this setting may help begin to reduce the negative impact of overdiagnosis in the older population.